Phialomyces macrosporus como agente bioprotetor contra Colletotrichum gloeosporioides e estimulante do crescimento em cafeeiro - Resende, Gilvane Aparecida de Carvalho (2015)
The development of biological methods for diseases control is becoming an important strategy in the search for more sustainable ways of managing coffee crop. The induction of plant resistance to pathogens is one of the means for biological control by antagonistic microorganisms. Some antagonists have the ability to stimulate the growth of the host plant. This dissertation consists of two complementary studies. In the first, we aimed to evaluate the inoculation of coffee seeds with antagonist fungus P. macrosporus as a bioprotector agent against C. gloeosporioides, and as a bio-stimulant for seedling growth. The treatments consisted of isolated or combined inoculations of both these fungi, in addition to a control treatment and a fungicide treatment. Initial root development, plant height and biomass production were evaluated at seedling stage. In the second study, we aimed to identify enzymatic processes influenced by inoculation of coffee roots with fungus P. macrosporus, and confirm its ability to induce resistance against C. gloeosporioides. Treatments consisted of isolated or combined inoculation of both these fungi on the roots of coffee seedlings, with or without intentional injury. In periods of 6, 12, 24 and 48 hours after completion of the inoculation procedures, the roots were collected to determine the activity of peroxidase, superoxide dismutase and chitinase. The inoculation of seeds with P. macrosporus provides bio-protection for coffee by inhibiting the action of pathogen C. gloeosporioides. In addition, we evidenced a bio-stimulant effect of P. macrosporus, which promotes higher root growth and biomass accumulation. The antagonism of P. macrosporus against C. gloeosporioides occurs via resistance induction, by stimulating the activity of the three studied enzymes. The activation of peroxidase is the main mechanism involved in the resistance induced by P. macrosporus.